Muscle-Building Exercise and Weapon Carrying and Physical Fighting Among U.S. Adolescent Boys - Ganson, Kyle T. (Journal of interpersonal violence, 2023)
This study aimed to determine the association between engagement in muscle-building exercise and weapon carrying and physical fighting among adolescent boys. Cross-sectional data from the 2019 Youth Risk Behavior Survey (U.S.) were analyzed (N = 4120). Muscle-building exercise was assessed based on the number of days reported in the past 7 days, recategorized into four levels of engagement (no engagement [0 days], low engagement [1–2 days], moderate engagement [3–5 days], and high engagement [6–7 days]). Three forms of weapon carrying (general, on school grounds, gun carrying) and two forms of physical fighting (general, on school grounds) were assessed. Five logistic regression analyses with adjusted odds ratios (AOR) and 95% confidence intervals (CI) were used to determine the association between engagement in muscle-building exercise and weapon carrying and physical fighting, while adjusting for relevant demographic and control variables. Over 75% of participants reported engaging in muscle-building exercise. One in five (19.8%) participants reported any general weapon carrying in the past 30 days, 3.3% reported any weapon carrying at school in the past 30 days, 6.5% reported any gun carrying in the past 12 months, 28.0% reported any general physical fighting in the past 12 months, and 10.7% reported any physical fighting at school in the past 12 months. Logistic regressions showed that, compared to no engagement, participants who reported high engagement of muscle-building exercise had higher odds of general weapon carrying (AOR 2.18, 95% CI 1.54–3.07), gun carrying (AOR 2.12, 95% CI 1.23–3.64), and general physical fighting (AOR 2.07, 95% CI 1.53–2.79). These are novel findings that add to a growing literature related to engagement in muscularity-oriented behaviors among males. Prevention and intervention efforts are needed to ensure that adolescent boys engage in muscle-building exercise in ways that are not harmful and to reduce weapon carrying and physical fighting.